Stereo-EEG exploration in the insula/operculum in paediatric patients with refractory epilepsy. (May 2020) - Kappen, Pablo; Eltze, Christin; Tisdall, Martin; Cross, J. Helen; Thornton, Rachel; Moeller, Friederike
Highlights: I/O region is involved in 64% of all SEEG paediatric with complex epilepsy. Focal tonic and hypermotor seizures are often seen in children with I/O involvement. It's difficult to distinguish I/O onset and propagation on non-invasive diagnostics. SEEG in the I/O is a safe investigation, even with many electrodes in the I/O. I/O surgery is safe with good outcome, but with high rates of transient deficit. Abstract: Purpose: Failure to recognise involvement of the insula / opercula (I/O) region is associated with poor outcome in epilepsy surgery. Recognition is challenging due to high connectivity with adjacent structures resulting in variable and misleading semiology, often subjective and therefore likely to be underreported by children. In this study we explored prevalence and characteristics of I/O involvement in paediatric patients undergoing sEEG exploration. Method: We retrospectively included all consecutive patients undergoing sEEG at our centre between 11/2014 and 01/2018 with at least three contacts within I/O and excluded those with undetermined seizure onset zone (SOZ) by sEEG. We divided patients into three groups: 1) SOZ in I/O, 2) spread to I/O and 3) no I/O involvement. We compared pre-invasive characteristics, sEEG results, surgery and outcome for each group. Results: 29 of all 53 consecutive patients had an identified SOZ by sEEG and at least three contacts within the I/O and were included. 41% had I/O SOZ, 38% had I/O spread and 21% had no I/O involvement. Insula associated symptoms described in adult literature were not statistically different between the three groups. Complications due to sEEG were low (2 of 53 patients). Following I/O surgery, 63% were seizure free while an additional 26% of patients achieved seizure reduction. Postoperative deficits were seen in 75% of the patients but completely resolved in all but one patient. Conclusions: Our data suggest an important role of the I/O region with frequent onset or propagation to the I/O region (at least 64% of all 53 sEEG cases). Semiology appears less specific than in adults. Insula depth electrode insertion is safe with subsequent good surgical outcomes albeit common transient deficits.